Digital Leadership: Challenges and Opportunities in the Era of Technology - Arees, Bushara Ahmed Sheabo (Journal of Ecohumanism, 2025)
This study aims to highlight the concept of digital leadership by analyzing the opportunities and challenges leaders face in the digital age. The researcher utilized a descriptive-analytical method and employed a questionnaire to collect data distributed among public and private sector participants. The findings revealed that resistance to change and lack of digital skills are primary challenges. Conversely, leveraging data analytics tools, digital collaboration platforms, and enhancing infrastructure through training were identified as key opportunities to improve operational efficiency and enable informed decision-making that fosters transparency and innovation.